Hallyu Stars in the Philippines: Effects of Brand and Endorser’s Credibility on Filipino Purchase Intention - Rono, Eunizer Aldrich A.; Lacap, Jean Paolo; Quipia, Jeren B.; Paral, Albert John C.; Sablas, Mary Devine L.; Coro, Nicanor Jayson M. (Jurnal The Messenger, 2024)
Introduction: There has been a notable rise in the popularity of K-pop endorsers within the landscape of Philippine advertising, influencing Filipino consumers' purchase intentions. Therefore, this study aims to examine the mediating effect of attitude toward a brand on the relationship between brand credibility, endorser credibility, and consumers' purchase intentions. Methods: The participants of the study were Filipino internet service subscribers, and they were selected using purposive sampling technique. The approach used in this study was quantitative research and causal-predictive approach while the partial least squares-structural equation modeling (PLS-SEM) was used to estimate the relationships of the proposed model. Findings: The results showed that an endorser's credibility significantly influences consumers’ purchase intention and attitude towards a brand. On the other hand, the relationship between brand credibility and purchase intention is not supported. However, there is a significant relationship between brand credibility and attitude towards a brand. The relationship between attitudes towards a brand and purchase intention is also supported. The mediation analysis revealed the importance of attitude towards a brand which tremendously mediates the relationship between brand credibility and endorser’s credibility leading to purchase intention. Originality: This study highlights the novel role of consumers' attitude as a mediator between endorser and brand credibility, shaping purchase intentions in the Philippine telecom industry through K-pop idol endorsements.